Automatic detection of airborne pollen: an overview - Jeroen Buters; Bernard Clot; Carmen Galán; Regula Gehrig; Stefan Gilge; François Hentges; David O’Connor; Branko Sikoparija; Carsten Skjoth; Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; et al. (Aerobiologia, 2024)
Pollen monitoring has traditionally been carried out using manual methods first developed in the early 1950s. Although this technique has been recently standardised, it suffers from several drawbacks, notably data usually only being available with a delay of 3–9 days and usually delivered at a daily resolution. Several automatic instruments have come on to the market over the past few years, with more new devices also under development. This paper provides a comprehensive overview of all available and developing automatic instruments, how they measure, how they identify airborne pollen, what impacts measurement quality, as well as what potential there is for further advancement in the field of bioaerosol monitoring.